Differences of cell surface marker expression between bone marrow- and kidney-derived murine mesenchymal stromal cells and fibroblasts - Cakiroglu, F.; Osbahr, J. W.; Kramer, J.; Rohwedel, J. (Cellular and Molecular Biology, 2016)
Mesenchymal stromal cells (MSC) are undifferentiated, multipotent adult cells with regenerative properties. They are particularly relevant for therapeutic approaches due to the simplicity of their isolation and cultivation. Since MSC show an expression pattern of cell surface marker, which is almost identical to fibroblasts, many attempts have been made to address the similarities and differences between MSC and fibroblasts. In this study we aimed to isolate murine MSC from bone marrow (BM) and kidney to characterize them in comparison to fibroblasts. Cells were isolated from murine kidney, BM and abdominal skin by plastic adherence and subsequently characterized by analysing their capability to build colony-forming unit-fibroblasts (CFU-F), their morphology, their proliferation, expression of telomerase activity and cell surface antigens as well as their differentiation capacity. Plastic adherent cells from the 3 mouse tissues showed similar morphology, proliferation profiles and CFU-F building capacities. However, while MSC from BM and kidney differentiated into the adipogenic, chondrogenic and osteogenic direction, fibroblasts were not able to do so efficiently. In addition, a tendency for lower expression of telomerase was found in the fibroblast population. Proliferating cells from kidney and BM expressed the MSC-specific cell surface markers CD105 and Sca-1 on a significantly higher and CD117 on a significantly lower level compared to fibroblasts and were thereby distinguishable from fibroblasts. Furthermore, we found that certain CD markers were specifically expressed on a higher level, either in BM-derived cells or fibroblasts. This study demonstrates that murine MSC isolated from different organs express certain specific markers, which enable their discrimination.